Evaluation of swallowing dysfunction in cases of locally advanced squamous cell carcinoma oral cavity pre and post treatment - Raj, Poonam; Gupta, Devendra Kumar; Samuel, Sameer; Singh, Sanajeet Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Oral cancer is one of the leading causes of dysphagia worldwide and is extremely common in Indian males. Swallowing dysfunction occurs due to the disease itself, its predisposing factors like tobacco chewing or smoking and the treatment undertaken which includes surgery of the primary as well as neck dissection and the adjuvant radiotherapy or chemoradiotherapy. This study was aimed to evaluate swallowing dysfunction in patients of locally advanced squamous cell carcinoma of the oral cavity prior to treatment and post-surgery and adjuvant therapy. Methods: 30 consecutive patients of advanced oral cavity squamous cell carcinoma planned for definitive treatment at a tertiary care center were randomly selected and included in the study. Evaluation of swallowing function was carried out using a dysphagia score and FEES (functional endoscopic evaluation of swallowing) initially during work-up for surgery, then three to four weeks post-surgery and finally six to eight weeks post adjuvant therapy. Results: Results of the study revealed that swallowing dysfunctions was observed in all the timelines of the study. Smoking, larger resection and advanced tumour stage were strong risk factors for postoperative aspiration and dysphagia complications in oral cancer patients. Multi-modality treatment also increased the incidence of post treatment dysphagia. Conclusions: Subjective and objective assessment of swallowing dysfunctions have to be considered as important tools to assess dysphagia pre and post treatment in oral cancer patients to detect swallowing dysfunction especially silent aspiration to institute early intervention in terms of swallow therapy.